IL-12α deficiency attenuates pressure overload-induced cardiac inflammation, hypertrophy, dysfunction, and heart failure progression - Bhattarai, Umesh; He, Xiaochen; Xu, Rui; Liu, Xiaoguang; Pan, Lihong; Sun, Yuxiang; Chen, Jian-Xiong; Chen, Yingjie (Frontiers in Immunology, 2023)
IL-12α plays an important role in modulating inflammatory response, fibroblast proliferation and angiogenesis through modulating macrophage polarization or T cell function, but its effect on cardiorespiratory fitness is not clear. Here we studied the effect of IL-12α on cardiac inflammation, hypertrophy, dysfunction, and lung remodeling in IL-12α gene knockout (KO) mice in response to chronic systolic pressure overload produced by transverse aortic constriction (TAC). Our results showed that IL12α KO significantly ameliorated TAC-induced left ventricular (LV) failure, as evidenced by a smaller decrease of LV ejection fraction. IL-12α KO also exhibited significantly attenuated TAC-induced increase of LV weight, left atrial weight, lung weight, right ventricular weight, and the ratios of them in comparison to body weight or tibial length. In addition, IL12α KO showed significantly attenuated TAC-induced LV leukocyte infiltration, fibrosis, cardiomyocyte hypertrophy, and lung inflammation and remodeling (such as lung fibrosis and vessel muscularization). Moreover, IL12α KO displayed significantly attenuated TAC-induced activation of CD4+ T cells and CD8+ T cells in the lung. Furthermore, IL12α KO showed significantly suppressed accumulation and activation of pulmonary macrophages and dendritic cells. Taken together, these findings indicate that inhibition of IL-12α is effective in attenuating systolic overload-induced cardiac inflammation, heart failure development, promoting transition from LV failure to lung remodeling and right ventricular hypertrophy.